2016
DOI: 10.1016/j.biortech.2015.11.080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fiber source and feed particle size on swine manure properties related to spontaneous foam formation during anaerobic decomposition

Abstract: Foam accumulation in deep-pit manure storage facilities is of concern for swine producers because of the logistical and safety-related problems it creates. A feeding trial was performed to evaluate the impact of feed grind size, fiber source, and manure inoculation on foaming characteristics. Animals were fed: (1) C-SBM (corn-soybean meal): (2) C-DDGS (corn-dried distiller grains with solubles); and (3) C-Soybean Hull (corn-soybean meal with soybean hulls) with each diet ground to either fine (374 μm) or coars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…What is clear from figure 1b is that by not including corn in the ration, the B diet produced a relatively distinct microbial community, while most of the other diets tended to be relatively similar in composition. These results contrast slightly with the results of Van Weelden et al (2016), who found that the microbial community was driven by both a carbon gradient within the manure and by the fiber source. However, fewer carbohydrate sources were used in that study, which allowed viewing of the carbon gradient without having that information confounded by the digestibility of the material within the pig as well as its microbial biodegradability, as was the case in this study.…”
Section: Microbial Communitycontrasting
confidence: 99%
“…What is clear from figure 1b is that by not including corn in the ration, the B diet produced a relatively distinct microbial community, while most of the other diets tended to be relatively similar in composition. These results contrast slightly with the results of Van Weelden et al (2016), who found that the microbial community was driven by both a carbon gradient within the manure and by the fiber source. However, fewer carbohydrate sources were used in that study, which allowed viewing of the carbon gradient without having that information confounded by the digestibility of the material within the pig as well as its microbial biodegradability, as was the case in this study.…”
Section: Microbial Communitycontrasting
confidence: 99%
“…Diets with DDGS contained 30.34% DDGS while the narasin diets contained 30 mg narasin/kg diet.. Gutierrez et al, 2013Gutierrez et al, , 2014aGutierrez et al, , 2014bKerr et al, 2013Kerr et al, , 2015aKerr et al, , 2015bKerr et al, , 2017Wu et al, 2016aWu et al, , 2016bWu et al, , 2016c and was not an objective of the current experiment. That said, a change in energy or nutrient digestibility (represented by a change in fiber digestibility in this experiment), can have (Kerr et al, 2006;Ziemer et al, 2009;Trabue and Kerr, 2014;Trabue et al, 2016b;Van Weelden et al, 2016a, and data obtained from this experiment are no exception. In contrast, the information on the impact of supplementing antibiotics or ionophores into the diet and subsequent effects on energy and nutrient digestibility is variable; where feeding antibiotics (Derick et al, 1986;Roth and Kirchgessner, 1993;Pilcher et al, 2015) or ionophores (Holzgraefe et al, 1985a(Holzgraefe et al, , 1985bMoore et al, 1986;Wuethrich et al, 1998) have had variable effects on N digestibility and balance.…”
Section: Manure Characteristics and Total Manure Nutrient Outputmentioning
confidence: 91%
“…Neither diet type or narasin supplementation affected manure GHG or GHG-equivalence emissions (P ≥ 0.45), and the only effect on manure C, N, or S emissions per unit of intake was a reduction in g N emissions per kg N intake for pigs fed the DDGS diet compared to pigs fed the CSBM diet (P ≤ 0.01), Table 7. The effect of feeding DDGS to pigs on the subsequent manure VOC, gas emissions, or GHG emissions was expected and has been discussed in depth in previous work from this laboratory (Kerr et al, 2006;Ziemer et al, 2009;Trabue et al, 2014Trabue et al, , 2016bVan Weelden et al, 2016a. Supplementation of antibiotics or ionophores have been shown to affect intestinal or fecal concentrations of fatty acids, indoles, or phenolics (Yokoyama et al, 1982;Hawe et al, 1992;Weuthrich et al, 1998) and ionophores have been shown to affect manure microbial ecology and in vitro emissions from swine manure (Cotta et al, 2001;Whitehead and Cotta, 2007;Andersen and Regan, 2014).…”
Section: Manure Voc and Gas Emissionsmentioning
confidence: 92%
See 1 more Smart Citation
“…Differences among means were considered significant at P ≤ .10. Although the effect of diet type and particle size on manure microbial community composition has been reported (Van Weelden, Andersen, Kerr, Trabue, & Pepple, 2016a), it was of interest to examine the relationship between manure C, N, and total VOCs and the microbial community structure. To accomplish this, the automated ribosomal intergenetic spacer analysis data reported by Van Weelden et al.…”
Section: Methodsmentioning
confidence: 99%